A new insight into the dynamics of fibre migration in ring spinning. Issue 4 (3rd April 2019) - Singh, Charanpreet; Gordon, Stuart; Zhang, Shangyong; Wang, Xungai
Abstract: Fibre migration in yarns is thought to take place in the spinning triangle (ST), where high tensioned edge fibres tend to compete for a low tension state by displacing inner fibres outwards to occupy the core position – the tension mechanism. The angular alignment of fibres in the drafted roving – the geometric mechanism – is also considered to contribute to this movement. Although there is an understanding of the mechanisms of fibre migration, the outward movement of core fibres, from a low to high tension state and through a thick web of gripped fibres – moving inwards – has not been fully understood. In this study, we have attempted to reanalyse the classical migration mechanism from a new perspective and establish its relationship with a real ST using a new reflective imaging technique. The study findings suggest that pre-twist region in the ST, which is generally considered to be stable at one location, shows a rather dynamic oscillatory movement – a result of continuous change in ST tension profile. Spinning trials were conducted to confirm a relationship between pre-twist movement and degree of fibre migration.